Factors contributing to the non-use of pharmacological pain relief methods by midwives during the intrapartum period on nulliparous women in the North West Province, South Africa - Mashala, Nthabiseng Jeniffer (My University, 2023)
Background: Pharmacological pain relief management is one of the effective methods of relieving pain during the intrapartum period. The ideal pharmacological pain relief methods must be safe, and effective and should not interfere with the labour mother. But, very few pregnant women experience pharmacological pain relief methods during labour. Aim: To determine factors contributing to the non-use of pharmacological pain relief methods by midwives during the intrapartum period on nulliparous women in selected hospitals in the North West Province of South Africa. Method/design: The study applied a quantitative, descriptive design to investigate factors contributing to the non-use of pharmacological pain relief. A total population sampling method was used to sample 93 midwives. A self-designed questionnaire was used to collect data and with the use of descriptive statistical analysis to analyse the data obtained. Permission to collect data was obtained from the North West Department of Health, the District office, Hospital Chief Executive Officer and ethical clearance was obtained from the Turfloop Research Ethics Committee. The study ensured the reliability and validity of the data collection instrument by conducting a pretest to identify errors. Results: The majority of midwives, 55.9% agreed that pain management is important and 46.2% agreed that mothers should be given pain relief. The results from the study have shown that factors contributing to the non-use of pharmacological pain relief were: a shortage of pharmacological pain relief, the unavailability of equipment, a shortage of staff, the lack of in-service training and the side effects of the medication administered. Conclusion: The unavailability of drugs and equipment, concerns about the side effects, and a lack of in-service training were identified as factors contributing to the non-use of pharmacological pain relief. Nursing management should enforce in-service training at least every second month and midwives must be encouraged to advance their skills. The National Department of Health (NDoH) should include detailed pain management during delivery, in its guidelines
Thesis (M.A. (Nursing)) -- University of Limpopo, 2023
Keywords: Pharmacological; Pain relief; Intrapartum; Nulliparous; Midwives; Analgesia; Pharmacology; Midwives; Pain -- Treatment